PARTISIPASI MASYARAKAT SEBAGAI INDIKATOR KEBERLANJUTAN PENGELOLAAN BANK SAMPAH (PENERAPAN DI KELURAHAN GEDUNG AIR BANDAR LAMPUNG) - Puspita Sari, Devi; Septiana, Ita Fauzia; Putri, Reza Kurnia; Tresiana, Novita; Duadji, Noverman; Krisnawati, Linda; Nirwanto, Nirwanto; Elizarwati, Elizarwati (Faculty of Economics and Business Lampung University, 2023)
Participation is the participation of a person or group of people in an activity. Participation is an empowerment program that should cover the entire process from start to finish. The methods used in the implementation of community service are: 1) observation and planning stage, 2) implementation stage, 3) evaluation stage. The purpose of this service is that it is hoped that the establishment of a waste bank can be beneficial for improving the community's economy, cleanliness and ecological benefits that require community support so that the waste bank program can be implemented optimally which will have an economic impact as compost or fertilizer which can provide opportunities for the community to work through waste empowerment. The results of this dedication show that waste management through the waste bank program in the Gedong Air sub-district, Bandar Lampung city, has been very positively received by the community and school students in the vicinity. However, there are still obstacles such as low community participation in the program. Therefore, it is necessary to socialize waste banks regularly to increase public understanding and awareness of the importance of waste management.